Hukum Suami Hilang Istri Nikah Lagi - zulva nisaul; Gefi Melyana saputri; Sudirman (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Marriage is one of the sacred and important moments in human life. A person who carries out a marriage means he is ready to perfect half of his religion by forming a happy family. In married life, the loss of a husband can be a very painful and confusing experience for the wife. When a husband disappears without a trace, either for unknown reasons or unforeseen circumstances, wives are often faced with deep uncertainty. This research uses a type of library research method with a descriptive qualitative approach. The results of the research are that a wife will remain the legal wife of a mafqud husband. According to Imam Hambali's opinion, when a wife is abandoned by her husband for a long time and feels emotionally disadvantaged, she has the right to demand a divorce. In these conditions, Islam provides a way out for wives, namely allowing them to divorce from their husband whose whereabouts are unclear. According to Imam Syafi'i, it is 90 years in Qoul Qodim and 4 years in Qoul Jadid. Apart from that, there is a view based on the Compilation of Islamic Law, namely 2 years.